2020
DOI: 10.1029/2020gc009159
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Viscous Anisotropy in the Upper Mantle and Its Geodynamic Implications

Abstract: Asthenospheric shear causes some minerals, particularly olivine, to develop anisotropic textures that can be detected seismically. In laboratory experiments, these textures are also associated with anisotropic viscous behavior, which should be important for geodynamic processes. To examine the role of anisotropic viscosity for asthenospheric deformation, we developed a numerical model of coupled anisotropic texture development and anisotropic viscosity, both calibrated with laboratory measurements of olivine a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
11
1
Order By: Relevance
“…The weakening is thus about a half of the predicted by SPO in our models, while the directional variations linked to LPO claimed by Király et al. ( 2020 ) can be up to two larger than what observed in our two‐phase aggregates and DEM models (Figure 7 ). This implies that an aggregate with mechanically anisotropic crystals should be more susceptible to changes in flow directions than when only isotropic SPO‐related fabrics are present.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The weakening is thus about a half of the predicted by SPO in our models, while the directional variations linked to LPO claimed by Király et al. ( 2020 ) can be up to two larger than what observed in our two‐phase aggregates and DEM models (Figure 7 ). This implies that an aggregate with mechanically anisotropic crystals should be more susceptible to changes in flow directions than when only isotropic SPO‐related fabrics are present.…”
Section: Discussioncontrasting
confidence: 55%
“…Recent numerical studies demonstrated that anisotropy related to lattice preferred orientation (LPO) in olivine crystals can yield a weakening of about ω = 30% in the shear direction, and up to one order of magnitude viscosity variations depending on the dominant slip system (Király et al, 2020). The weakening is thus about a half of the predicted by SPO in our models, while the directional variations linked to LPO claimed by Király et al (2020) can be up to two larger than what observed in our two-phase aggregates and DEM models (Figure 7). This implies that an aggregate with mechanically anisotropic crystals should be more susceptible to changes in flow directions than when only isotropic SPO-related fabrics are present.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, only lateral heterogeneities in the lithospheric structure, which may include local weak zones or a pre‐existing variations in lithosphere thickness, are expected to have an impact on lithospheric thinning and associated surface heat flux. In addition, anisotropic lithosphere viscosity may affect the position and dynamics of dripping instabilities (Király et al., 2020; Lev & Hager, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, only lateral heterogeneities in the lithospheric structure, which may include local weak zones or a pre-existing variations in lithosphere thickness, are expected to have an impact on lithospheric thinning and associated surface heat flux. In addition, anisotropic lithosphere viscosity may affect the position and dynamics of dripping instabilities (Király et al, 2020;Lev & Hager, 2008). 2020)) for 150 km thick cratons, we would expect maximum relative heat flux anomalies of about 20% and 60%, respectively (Figure 4).…”
Section: Discussionmentioning
confidence: 97%